Polycentrism: A case study on water access and management in community-based water tenure in Makopa and Simukale villages - Carol Emma Mweemba; van Koppen, Barbara; Amarnath, Giriraj (2022)
The objective of this study is to map community solutions to deal with climate variability and how information is mobilized into or interfaces with the next layer of government interventions that brings new perspectives in understanding how local solutions can be better mobilized into external solutions to climate change adaptation through horizontal and vertical integration processes, with a focus on living community-based water tenure in rural Zambia. This study intends to highlight access rights and management to community water resources and land in rural areas of two low-income communities. This is achieved by comparing bottom-up living integrated customary land and water tenure and vertical and horizontal decision-making processes at different levels of governance